The World Health Organization Global Benchmarking Tool an Instrument to Strengthen Medical Products Regulation and Promote Universal Health Coverage - Khadem Broojerdi, Alireza; Baran Sillo, Hiiti; Ostad Ali Dehaghi, Razieh; Ward, Mike; Refaat, Mohamed; Parry, Jane (Frontiers in Medicine, 2020)
National regulatory authorities (NRAs) are the gatekeepers of the supply chain of medical products, and they have a mandate to ensure the quality, safety and efficacy of medicines, vaccines, blood and blood products, medical devices, including diagnostics and traditional or herbal medicines. However, the majority of the world’s regulators are still struggling to reach a level of maturity, whereby they have a stable, well-functioning and integrated regulatory system. The World Health Organization (WHO) has developed a Global Benchmarking Tool (GBT) as part of its five-step capacity building program to assist NRAs, using the tool, they can benchmark their own strengths and areas of weakness, and then engage in a formal benchmarking process together with WHO and international experts in order to formulate an effective and workable institutional development plan. The GBT is comprehensive across the entire product life cycle and allows benchmarking to be customized to the needs of the NRA. It has evolved from decades of experience using a variety of benchmarking tools, within WHO and other stakeholder organizations. By the end of September 2019, 24 countries had undergone formal benchmarking, and a further 52 countries had used the GBT to conduct self-benchmarking exercises assisted by WHO.